Developmental dyslexia in Hindi readers: Is consistent sound‐symbol mapping an asset in reading? Evidence from phonological and visuospatial working memory. (20th August 2019) - Bajre, Purnima; Khan, Azizuddin
Abstract : Phonological processing deficit is a hallmark of developmental dyslexia indicating a core cognitive dysfunction. Importance of working memory in reading and its association with the tasks measuring phonological processing is also debated in research. The present study investigates the role of working memory, phonological, and orthographic processing in Hindi‐speaking dyslexic children (22 dyslexic and 23 control, of Grade 4). Hindi has a consistent symbol‐sound mapping with an extensive list of visually complex graphemes. Although consistent symbol‐sound mapping facilitates reading, graphemic complexity has its cost on memory. A range of tasks measuring phonological processing, working memory, and orthographic knowledge was designed and administered. Dyslexic children scored significantly lower than controls not only on working memory tasks but also on the tasks of phonological processing and orthographic knowledge. Moreover, the difference in working memory between dyslexic and normal children was more pronounced with increased task complexity. These results highlight complex relationships between working memory, phonological and orthographic processing together with visual attentional processing in Hindi, that contribute to the reading deficits encountered by children with dyslexia. Their respective contributions are considered in the discussion with some of the visual and phonological features of Hindi orthography and their associated effects in reading.